Detection of hepatocellular carcinoma methylation markers in salivary DNA - Mezzacappa, Catherine; Wang, Zhanwei; Lu, Lingeng; Risch, Harvey; Taddei, Tamar; Yu, Herbert (Bioscience reports, 2024)
Background: Alterations to DNA methylation have been identified in both hepatocellular carcinoma (HCC) tumor and circulating DNA from affected individuals. These markers have potential utility in HCC screening. Adherence to HCC screening is poor and acceptable HCC screening tests are needed. Methods: A feasibility study was performed on a subset of case patients and control subjects from a prior study of risk factors for HCC. Case patients (n=12) included adults aged 47–85 years with a first diagnosis of HCC between 2011 and 2016 and without viral hepatitis. Control subjects (n=12) were matched on age, sex, and state of residence. Participants provided saliva samples for DNA genotyping. Log fold change in salivary DNA methylation at 1359 CpG sites representing 25 candidate genes previously associated with HCC was compared across case patients and control subjects. Results: The quantity of DNA ranged from 9.65 to 257.79 μg. The purity of DNA isolates was good, with mean OD260/280 ratio of 1.78 (SD: 0.14). Of 25 candidate genes, 16 had at ≥1 CpG site with detectable differences in methylation across HCC case patients and control subjects. Sites differentially methylated in HCC case patients included genes encoding tumor suppressors (PRDM2, RUNX3, p15/16, and RASSF1/5), regulators of cell cycle progression (DAPK1 and TP73), and DNA repair (MGMT and GSTP1). No associations met the significance threshold 3.7 × 10−5 required for multiple comparisons. Conclusions: Salivary DNA may be a feasible alternative to blood samples in the era of novel DNA-based screening tests for HCC. The ease of saliva-based testing supports further investigation of its potential.